Implementasi Manajemen Pembinaan dan Pengembangan Peserta Didik di MTs Nurul Huda Kauditan 2 Kecamatan Kauditan Kabupaten Minahasa Utara - Adinda Dewi Siti Khodijah; Shinta Nento; Hasnil Oktavera; Kusnan Kusnan (Journal of Islamic Education Leadership, 2023)
The Implementation of Management of Student Guidance and Development at MTs Nurul Huda Kauditan 2. This study aims to analyze the Implementation of Student Management and the supporting and inhibiting factors of student management at MTs Nurul Huda Kauditan 2. The type of research used is descriptive qualitative. Data were obtained through observation, interviews, and documentation, this study’s stages of data analysis consisted of data collection, data reduction, data presentation, and conclution. This research show that the management of guidance and development at the MTs Nurul Huda Kauditan 2 is well implemented following the plans made through the New Academic Year Preparatory Meeting, which discusses cirricular and extracurricular activities to be carried out. Furthermore, the supporting factors for student management are coaches who are experts in their fields, the student’s enthusiasm, and the support of students’ parents. In contrast, the inhibiting factors are the lack of complete facilities and infrastructure, in this case, inadequate library book collections and the absence of a sciense laboratory to fully support the guidance and development of students